Analisis Bibliometrik Profesionalisme Guru: Penelitian Menggunakan Aplikasi VOSViewer - Patty, Elyakim Nova Supriyedi; Iriyani, Sri Astuti; Hadi, Heri Sopian; Abdulrahim, Abdulrahim; Irhas, Irhas (Jurnal Simki Pedagogia, 2023)
This study aims to systematically analyze and demonstrate bibliometric data analysis using VOSViewer. This study uses a qualitative descriptive method to describe the data on teacher professionalism. So it can be concluded that teacher professionalism can be combined with other fields to be studied. This study presents an analysis of data regarding teacher professionalism and its development over sixteen years (2008–2023) by utilizing the mapping tool in VOSViewer. To describe the performance of bibliometric analysis by producing a network visualization of the selected topic using a qualitative descriptive method. From the search results, 989 relevant published journals were found, ranging from 2008–2023, which were then grouped into 16 categories according to the year of publication. The results of this research on professional teachers found that the most published articles were in 2016-2021. We can see items supporting the formation of a professional as a teacher. Therefore it is necessary to carry out activities or support to increase teacher professionalism such as conducting classroom action research (PTK), conducting coaching, participating in MGMP and other activities.